The neuron-astrocyte-microglia triad in a rat model of chronic cerebral hypoperfusion: protective effect of dipyridamole - Lana, Daniele; Melani, Alessia; Pugliese, Anna Maria; Cipriani, Sara; Nosi, Daniele; Pedata, Felicita; Giovannini, Maria Grazia (Frontiers in Aging Neuroscience, 2014)
Chronic cerebral hypoperfusion during aging may cause progressive neurodegeneration as ischemic conditions persist. Proper functioning of the interplay between neurons and glia is fundamental for the functional organization of the brain. The aim of our research was to study the pathophysiological mechanisms, and particularly the derangement of the interplay between neurons and astrocytes-microglia with the formation of “triads”, in a model of chronic cerebral hypoperfusion induced by the 2-vessel occlusion (2VO) in adult Wistar rats (n=15). The protective effect of dipyridamole given during the early phases after 2VO (4 mg/kg/day i.v., the first 7 days after 2VO) was verified (n=15). Sham-operated rats (n=15) were used as controls. Immunofluorescent triple staining of neurons (NeuN), astrocytes (GFAP) and microglia (IBA1) was performed 90 days after 2VO. We found significantly higher amount of “ectopic” neurons, neuronal debris and apoptotic neurons in CA1 Str. Radiatum and Str. Pyramidale of 2VO rats. In CA1 Str. Radiatum of 2VO rats the amount of astrocytes (cells/mm2) did not increase. In some instances several astrocytes surrounded ectopic neurons and formed a “micro scar” around them. Astrocyte branches could infiltrate the cell body of ectopic neurons, and, together with activated microglia cells formed the “triads”. In the triad, significantly more numerous in CA1 Str. Radiatum of 2VO than in sham rats, astrocytes and microglia cooperated in the phagocytosis of ectopic neurons. These events might be common mechanisms underlying many neurodegenerative processes. The frequency to which they appear might depend upon, or might be the cause of, the burden and severity of neurodegeneration. Dypiridamole significantly reverted all the above described events. The protective effect of chronic administration of dipyridamole might be a consequence of its vasodilatory, antioxidant and anti-inflammatory role during the early phases after 2VO.